The introduction, performance and status of Pinus halepensis, P. nigra and P. pinea in South Africa - Zwolinski J. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Mediterranean pine species have been planted in the Cape Colony from the beginning of European settlement in South Africa. One of the first introduced was P. pinea (XVI century) followed later by P. halepensis (early XIX century) and P. nigra (late XIX century). P. pinea and P. halepensis performed relatively well under harsh conditions of dry and cool climate. In stands, they could grow to almost 30 m in height. Since the beginning of the XX century, the two species have not been used for commercial tree planting any more because their growth is slower compared to other pines. They remain, however, important in landscaping in towns and cities as well as in tree planting projects on farms.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)